Development of a Rapid Sporulation Method of Fusarium graminearum Using Liquid Cultivation - Zhang, Xue (Plant disease, 2022)
Fusarium graminearum is an important fungus causing a variety of maize diseases, including stalk rot, ear rot, and sheath rot. However, conidia of F. graminearum are not easily obtained under normal culture conditions, which seriously affects the identification and pathogenicity assessment of the isolates and screening of resistance sources. This study was undertaken to develop and utilize a rapid sporulation technique of F. graminearum using liquid cultivation, which could meet the needs of various tests. The results show that the optimum conditions for sporulation of F. graminearum were as follows: culture medium, 0.154 mol/liter of saline; temperature, 28 to 30°C; incubation time, 96 h; initial pH, 9 to 10; illumination, continuous ultraviolet light; and shaking speed, 150 rpm. Using this culture method, conidial concentration of tested F. graminearum strains can reach >1.5 × 105 conidia/ml. Compared with the existing methods using mung bean and carboxylmethyl cellulose as matrix, saline is relatively inexpensive, and the culture process, relatively quick. Overall, this study provided a systematic, rapid, and simple method to obtain a large number of conidia of F. graminearum